Single-Board Computers in Education: A systematic literature review (Research, Society and Development, 2021)
Single-Board Computers (SBCs) are single-board computers, which have low cost, reduced energy consumption and small size. They can be applied in various situations, for example in academic projects and data centers. This article presents the result of a Systematic Literature Review (RSL) that sought to identify, at national and international levels, the contribution of SBCs as tools to support teaching, in published articles, in journals and conferences, between the years 2017 and 2021. A central question and three specific ones were defined to guide the research, together with the application of the inclusion and exclusion criteria, making it possible to carry out the selection and extraction of the data. The results achieved show that the Raspberry Pi is the SBC that has been most used, mainly in the areas of science, technology, engineering and mathematics teaching, through the following main approaches: gamification, courses, virtual laboratories and online platforms.